Comparison of Genetic Variants and Manifestations of OTUD6B-Related Disorder: The First Mexican Case - Maria Elena Romero-Ibarguengoitia MD, MS, PhD; Consuelo Cantú-Reyna MD, MS; Dalia Gutierrez-González MD; Héctor Cruz-Camino BS; Arnulfo González-Cantú MD, MSC; Miguel Angel Sanz Sánchez MD (SAGE Publishing, 2020)
The intellectual disability syndrome characterized by seizures and dysmorphic features was initially described in 2017 and was associated with genetic variants in the OTUD6B gene, identified by exome sequencing (ES) in a large cohort. This multisystem disorder primarily affects the central nervous system, the gastrointestinal, and the skeletal systems. In this article, we describe the first Mexican patient diagnosed by ES. The homozygous c.433C>T (p.Arg145*) variant of the OTUD6B gene confirmed this intellectual disability syndrome. In addition to seizures and other more frequently reported manifestations of this condition, this is the third patient with associated hypothyroidism and hypogammaglobulinemia, underscoring the value of screening for these conditions in other patients. The current challenge with this patient is to ensure medical management of his seizures and provide him with a better quality of life. The possibilities of additional therapeutic approaches may increase by understanding the physiopathology of the involved pathways.